A prospective observational study on maternal diet pre- and post-GDM diagnosis and pregnancy outcomes in individuals with/without GDM - Ying Liu; Nafei Guo; Yawen Dai; Lan Zhang; Junying Li; Xuemei Li; Hui Jiang (BMC Pregnancy and Childbirth)
Abstract Aims To investigate (1) the association between maternal dietary choices during the first and second trimesters and the diagnosis of gestational diabetes mellitus (GDM), (2) the association between a GDM diagnosis and dietary choices during pregnancy, and (3) the differences in pregnancy outcomes between individuals with and without GDM. Methods A prospective cohort study. Pregnant individuals with singleton pregnancy aged 19 ∼ 44 years, without severe pregnancy complications were enrolled in the study. Dietary data were collected at three time points during routine antenatal appointments: 8 ∼ 12 weeks gestation(n = 993), 20 ∼ 24 weeks gestation(n = 732), and 32 ∼ 36 weeks gestation(n = 536). GDM diagnosis and pregnancy outcomes were collected during follow-up from the electronic medical record (EMR). Results A total of 93 participants (12.9%) were diagnosed with GDM. Livestock and poultry meat intake during the second trimester were associated with an increased risk of developing GDM (aOR 1.371, 95%CI 1.070–1.756, P = 0.013), and a GDM diagnosis may lead to decreased intake of cereals and its products (P = 0.001), potatoes and its products (P < 0.001), and fruit (P = 0.002) and increased intake of fish, shrimp and shellfish (P = 0.001), eggs (P = 0.015), and milk and milk products (P = 0.011) in the third trimester. Individuals with GDM related to lower risk of excessive gestational weight gain (aOR 0.384, 95%CI 0.188–0.646, P = 0.001) but may increase the risk of fetal macrosomia (aOR 3.873, 95%CI 1.364–10.996, P = 0.011). Conclusions Understanding maternal dietary choices around GDM diagnosis is crucial for accurate nutritional assessment and effective education programs. While our findings suggest dietary changes may occur post-diagnosis, further research is needed to confirm these patterns and the potential benefits of early dietary counseling for individuals with GDM.